FBXW7 suppresses HMGB1-mediated innate immune signaling to attenuate hepatic inflammation and insulin resistance in a mouse model of nonalcoholic fatty liver disease - Cheng Zhang; Feng Chen; Li Feng; Qun Shan; Gui-Hong Zheng; Yong-Jian Wang; Jun Lu; Shao-Hua Fan; Chun-Hui Sun; Dong-Mei Wu; Meng-Qiu Li; Bin Hu; et al. (BMC, 2019)
Abstract Background Innate immune dysfunction contributes to the development and progression of nonalcoholic fatty liver disease (NAFLD), however, its pathogenesis is still incompletely understood. Identifying the key innate immune component responsible for the pathogenesis of NAFLD and clarifying the underlying mechanisms may provide therapeutic targets for NAFLD. Recently, F-box- and WD repeat domain-containing 7 (FBXW7) exhibits a regulatory role in hepatic glucose and lipid metabolism. This study aims to investigate whether FBXW7 controls high-mobility group box 1 protein (HMGB1)-mediated innate immune signaling to improve NAFLD and the mechanism underlying this action. Methods Mice were fed a high-fat diet (HFD) for 12 or 20 weeks to establish NAFLD model. Hepatic overexpression or knockdown of FBXW7 was induced by tail-vein injection of recombinant adenovirus. Some Ad-FBXW7-injected mice fed a HFD were injected intraperitoneally with recombinant mouse HMGB1 to confirm the protective role of FBXW7 in NAFLD via inhibition of HMGB1. Results FBXW7 improves NAFLD and related metabolic parameters without remarkable influence of body weight and food intake. Moreover, FBXW7 markedly ameliorated hepatic inflammation and insulin resistance in the HFD-fed mice. Furthermore, FBXW7 dramatically attenuated the expression and release of HMGB1 in the livers of HFD-fed mice, which is associated with inhibition of protein kinase R (PKR) signaling. Thereby, FBXW7 restrains Toll-like receptor 4 (TLR4) and receptor for advanced glycation end products (RAGE) signaling in HFD-fed mouse livers. In addition, exogenous HMGB1 treatment abolished FBXW7-mediated inhibition of hepatic inflammation and insulin resistance in HFD-fed mouse livers. Conclusions Our results demonstrate a protective role of FBXW7 in NAFLD by abating HMGB1-mediated innate immune signaling to suppress inflammation and consequent insulin resistance, suggesting that FBXW7 is a potential target for therapeutic intervention in NAFLD development.